A WAY TO PRODUCE NATIONAL CLOTHES PATTERN DESIGNED IN HARMONY OF EUROPEAN AND ASIAN FASHION IN A COST- EFFECTIVE WAY WITH MODERN CAD/CAM SYSTEMS (International journal of artificial intelligence, 2025)
The analysis in this article shows that the design and production of women's clothing in modern CAD/CAM systems has not been established in our Republic at the required level. Therefore, it is necessary to improve the quality and design of clothing, effectively use natural and seasonal fabrics, and build an optimal design based on modern design programs. It is envisaged to harmoniously reflect the oriental nationality in modern European women's clothing, that is, to use the assortment of national fabrics as decoration, to bring back the increasingly declining gold embroidery patterns into fashion, and to widely use national embroidered copies.